2022
DOI: 10.1136/bmjsem-2021-001297
|View full text |Cite
|
Sign up to set email alerts
|

Nearly half of patients with chronic tendinopathy may have a neuropathic pain component, with significant differences seen between different tendon sites: a prospective cohort of more than 300 patients

Abstract: ObjectivesIdentifying the prevalence of neuropathic pain components in patients with chronic tendinopathy conditions using the Self-Administered Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS) questionnaire.MethodsPatients with chronic tendinopathy and ‘tendon-like’ conditions treated within a single hospital outpatient clinic specialising in tendinopathy were identified. Pain scores, plus global function patient-reported outcome measures (5-Level version of EuroQol-5 Dimension and Musculoskeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…However, there were limitations identified that impact the applicability of conclusions to clinical practice. All but two studies (Wheeler, 2022a; Wheeler et al., 2022) failed to consider confounding subject baseline psychological comorbidities such as centrally sensitised pain states, anxiety and depression, that can adversely impact GTPS symptomology (Boyd et al., 2020; French et al., 2019; Wheeler, 2022b), and potential SWT treatment response (Peinemann et al., 2013; Walker et al., 2006). Consistent with the literature (Appendixs and ), clinical assessment and diagnosis of GTPS varied across included studies (Appendix ), reducing the likelihood that GTPS was the primary pathology being treated with SWT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were limitations identified that impact the applicability of conclusions to clinical practice. All but two studies (Wheeler, 2022a; Wheeler et al., 2022) failed to consider confounding subject baseline psychological comorbidities such as centrally sensitised pain states, anxiety and depression, that can adversely impact GTPS symptomology (Boyd et al., 2020; French et al., 2019; Wheeler, 2022b), and potential SWT treatment response (Peinemann et al., 2013; Walker et al., 2006). Consistent with the literature (Appendixs and ), clinical assessment and diagnosis of GTPS varied across included studies (Appendix ), reducing the likelihood that GTPS was the primary pathology being treated with SWT.…”
Section: Discussionmentioning
confidence: 99%
“…As GTPS symptoms are often aggravated by sitting, walking, climbing stairs and with ipsilateral side lying (Fearon et al., 2012; McAuliffe et al., 2020), sufferers often complain of reduced mobility, sleep and function (Grimaldi & Fearon, 2015; Long et al., 2013). Consequently, GTPS has been linked with heightened levels of psychological and psychosocial dysfunction (Boyd et al., 2020; Ferrer‐Pena et al., 2019b; McAuliffe et al., 2020) leading to central sensitisation (French et al., 2019; Wheeler, 2022b) and a subsequent chronic pain state (Boyd et al., 2020; Ferrer‐Pena et al., 2019a), further reducing the likelihood of symptom resolution (Anderson et al., 2014; Main et al., 2008). Given the detrimental impact of GTPS on the quality of life, optimising management strategies becomes imperative.…”
Section: Introductionmentioning
confidence: 99%